1994
DOI: 10.2527/1994.7241013x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of grazing cattle and sheep together and separately on animal performance and forage quality

Abstract: Cattle and sheep grazed together and separately from April to October during 3 yr. Initial forage composition was 29% Kentucky bluegrass (Poa pratensis L.), 11% white clover (Trifolium repens L.), and 60% weeds. There were six Angus cow-calf pairs or six ewes (1/2 Dorset x 1/4 Finn x 1/4 Rambouillet) with 11 lambs per each of three pasture replications for single animal species. Six cow-calf pairs plus six ewes and 11 lambs grazed in each of three replications of the mixed animal species treatment. There were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 12 publications
3
26
0
Order By: Relevance
“…Thus, grazing by goats has been found to have positive effects on following sheep grazing, as the proportion of clover in the pasture increased (del Pozo et al 1998). Sheep may feed on dung pats of cattle and vice versa, decreasing the amount of nutrient and pasture space lost (Abaye et al 1994;Forbes and Hodgson 1985;Fraser et al 2007). Co-grazing may also lead to increased daily liveweight gains of both animal species involved (Nolan and Connolly 1989).…”
Section: Grazing Management and Diversitymentioning
confidence: 99%
“…Thus, grazing by goats has been found to have positive effects on following sheep grazing, as the proportion of clover in the pasture increased (del Pozo et al 1998). Sheep may feed on dung pats of cattle and vice versa, decreasing the amount of nutrient and pasture space lost (Abaye et al 1994;Forbes and Hodgson 1985;Fraser et al 2007). Co-grazing may also lead to increased daily liveweight gains of both animal species involved (Nolan and Connolly 1989).…”
Section: Grazing Management and Diversitymentioning
confidence: 99%
“…Indeed, this relationship depends on how the biomass is used by the grazing animals. Thus, careful consideration of the type of biomass present, the amount available to the animals (expressed either per kg of MW or kg of BW) and the amount actually exploited for their performance, is essential to better anticipate animal production in the pasture (Abaye et al, 1994;Allen et al, 2011). In the present study, mixed grazing had no effect on any chemical composition of the grass.…”
Section: Discussionmentioning
confidence: 51%
“…Mixed grazing could be an efficient strategy for goat production in the pasture, as their vulnerability to GIN and selective behaviour is superior to those of sheep (Goetsch et al, 2010;Rutter, 2010). Complementarity in the feeding behaviour of associated species is expected to lead to a better quality of available biomass and thus promote animal production (Abaye et al, 1994;Sehested et al, 2004). The behaviour of grazing cows is known to differ from that of goats, which are very selective (Fraser et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Goats following cattle and goats mixed with cattle were heavier. Abaye et al (1994) reported that lamb daily gain (0.23 kg/d), total gain (23 kg) and weaning weights (43 kg) were greater (p<0.01) and target weaning weights were reached 14 d earlier in the grazing season when both goat and cattle grazed together than when lambs were in pastures with sheep alone (18 kg/d, 19 and 38 kg, respectively). The fact that body weights in goats grazing alone decreased initially is most likely due to the goats being stressed because of being introduced to new pastures and an acclimation period.…”
Section: Discussionmentioning
confidence: 99%